Sistem Informasi Persediaan Bahan Baku Produksi Berbasis Website pada CV Deco Abadi Makassar - Amiruddin, Amiruddin; Gabriela Wong, Melinda Lady; Yuliana, Yuliana; Sari, Syahriah (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2024)
The management of raw materials at CV Deco Abadi Makassar has problems with checking goods, recording production raw materials, and communication between the warehouse and the company. Online information systems allow for systematic data processing that can be used to overcome these problems. This research aims to: 1) produce a website-based production raw material inventory information system at CV Deco Abadi Makassar; 2) obtain user responses regarding the website-based inventory information system at CV Deco Abadi Makassar that has been produced. This research uses data collection methods through observation and interviews with qualitative data analysis. Then, the design was carried out using a waterfall model consisting of requirements analysis, system design, implementation, and testing. The proposed features include item data input, inventory graphs, stock notifications, and user control. The research results show that 1) the design of a website-based production raw material inventory information system was designed through the stages of needs analysis, system design, implementation, and testing. 2) User responses regarding this information system are to the needs of CV Deco Abadi Makassar.